Evaluation of Soil Manipulation to Prepare Engineered Earthen Waste Covers for Revegetation. Issue 6 (1st November 2015) - Waugh, W. Joseph; Benson, Craig H.; Albright, William H.; Smith, Gregory M.; Bush, Richard P.
Abstract : Seven ripping treatments designed to improve soil physical conditions for revegetation were compared on a test pad simulating an earthen cover for a waste disposal cell. The field test was part of study of methods to convert compacted‐soil waste covers into evapotranspiration covers. The test pad consisted of a compacted layer of fine‐textured soil simulating a barrier protection layer overlain by a gravelly sand bedding layer and a cobble armor layer. Treatments included combinations of soil‐ripping implements (conventional shank [CS], wing‐tipped shank [WTS], and parabolic oscillating shank with wings [POS]), ripping depths, and number of passes. Dimensions, dry density, moisture content, and particle size distribution of disturbance zones were determined in two trenches excavated across rip rows. The goal was to create a root‐zone dry density between 1.2 and 1.6 Mg m −3 and a seedbed soil texture ranging from clay loam to sandy loam with low rock content. All treatments created V‐shaped disturbance zones as measured on trench faces. Disturbance zone size was most influenced by ripping depth. Winged implements created larger disturbance zones. All treatments lifted fines into the bedding layer, moved gravel and cobble down into the fine‐textured protection layer, and thereby disrupted the capillary barrier at the interface. Changes in dry density within disturbance zones were comparable for the CS and WTS treatments but were highly variable among POS treatments. Water content increased in the bedding layer and decreased in the protection layer after ripping. The POS at 1.2‐m depth and two passes created the largest zone with a low dry density (1.24 Mg m −3 ) and the most favorable seedbed soil texture (gravely silt loam). However, ripping also created large soil aggregates and voids in the protection layer that may produce preferential flow paths and reduce water storage capacity. Core Ideas: Soil‐forming and ecological processes are changing engineering properties of earthen covers. These changes may transform compacted soil designs into evapotranspiration covers. Ripping implements were tested as a way to enhance transformation of layered rock/soil covers. Disturbed soil volume, cover layer mixing, and change in dry density were greater for winged rippers. Ripping also created large soil aggregates and voids in compacted soil layers.